Aging, personality, and teaching aptitude in school grade physical education teachers - Bijender; Kuldeep Nara; Parveen Kumar (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. The primary objectives of the research were to examine the impact of aging on teaching aptitude, explore the association between personality traits and teaching effectiveness, and identify potential interactions between age, personality, and teaching aptitude.